DRAINAGE SYSTEM DESIGN OF THE LIGHT RAIL TRANSIT (LRT) ROAD RAWAMANGUN-PASAR PRAMUKA PHASE 1B STA 0+130 to 3+445 - Alfina Rahma Al-Banjary; Ratih Indri Hapsari (Jurnal Online Skripsi Manajemen Rekayasa Konstruksi (JOS-MRK), 2026)
Light Rapid Transit (LRT) is a modern and efficient public transportation system constructed at surface level to reduce traffic congestion and provide high accessibility. One of the critical components of LRT infrastructure is the drainage system, which serves to prevent water ponding on the rail tracks that could endanger safety and damage the electrical systems. This final project focuses on designing an effective drainage network for the LRT road segment between Velodrome and Pasar Pramuka Phase 1B, STA 0+130 to STA 3+445. The study includes hydrological and hydraulic analysis, covering rainfall intensity calculation, design flood discharge estimation with 25 years returns period, drainage channel design, and construction method planning. The proposed drainage cross-sections consist of U-Ditch channels with dimensions of 0.5 × 0.5 m and 0.8 × 0.8 m, as well as precast box culverts measuring 0.6 × 0.6 m and 0.8 × 0.8 m. This design refers to both technical and non-technical standards. The total estimated budget required for the construction of this drainage system is Rp9,491,653,696.92. The system is expected to manage stormwater runoff effectively and ensure the safety and operational reliability of the LRT route.